2018
DOI: 10.1074/jbc.ra117.001358
|View full text |Cite
|
Sign up to set email alerts
|

Nudt19 is a renal CoA diphosphohydrolase with biochemical and regulatory properties that are distinct from the hepatic Nudt7 isoform

Abstract: CoA is the major acyl carrier in mammals and a key cofactor in energy metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 57 publications
2
56
0
Order By: Relevance
“…1A). Indeed, one liter of autoinduced culture typically yielded about 15 mg of Nudt8 compared to the 70-100 mg of Nudt7 obtained per liter of standard E. coli culture [13]. To test the possibility that Nudt8 could hydrolyze CoA species, we expressed and purified the mouse enzyme as a 24 kDa protein with a C-terminal hexahistidine tag (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1A). Indeed, one liter of autoinduced culture typically yielded about 15 mg of Nudt8 compared to the 70-100 mg of Nudt7 obtained per liter of standard E. coli culture [13]. To test the possibility that Nudt8 could hydrolyze CoA species, we expressed and purified the mouse enzyme as a 24 kDa protein with a C-terminal hexahistidine tag (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test the possibility that Nudt8 could hydrolyze CoA species, we expressed and purified the mouse enzyme as a 24 kDa protein with a C-terminal hexahistidine tag (Fig. Analytical gel filtration analysis of recombinant mouse Nudt8 indicated that similar to Nudt7 [13], about 70% of the protein eluted as a monomer (Fig. Compared to recombinant Nudt7, Nudt8 was purified in significantly lower amounts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations